Adjudicative Bilateralism and Community Interests. (26th April 2021) - Bonafé, Beatrice I.
Abstract : The purpose of this essay is to explore the two main ways in which community interests have been taken into account in international adjudication. First, special procedural tools have been devised in order to accommodate the multilateral dimension of certain disputes into the traditionally bilateral scheme of international adjudication. It will be shown that such tools have been of little use for the protection of community interests. Second, legal relations engendered by community interests have been conceptualized in a bilateral manner so that they could fit adjudicative bilateralism. It may seem counterintuitive, but it will be maintained that this second avenue offers the most concrete, yet not entirely satisfactory, means to adjudicate community interests. Finally, the essay argues that the Monetary Gold rule proves a useful test to properly understand the different logic of these two avenues.